O direito dos acionistas de participar nos lucros sociais - Cometti, Marcelo Tadeu (2007)
The paper herein has the purpose to study the right of the shareholders to participate in the profits as a stabilization instrument of the relation of internal power in the companies. For this purpose, this paper will be divided in three chapters.The first chapter analyzes the rules set forth in Law 6,404/76 and further amendments, which will establish the criteria for the ascertaining and destination of profits. The concept of profit, the period whereby the profits are ascertained and the accounting instruments for their determination are tried to be determined herein. Considering the fact that not all of the profit ascertained by the company is destined to the shareholders as dividends, this referred chapter brings up the study of part of the profits which is destined to the payment of the statutory interest, as well as the creation or maintenance of reserves or profits retention. The second chapter presents the several groups of shareholders of a company and the relation of power existing among them. It is analyzed in this context the fundamental rights (direitos essenciais) and consequently the right of the shareholder to participate in the profits. It is also analyzed in this chapter the legal nature of the right to participate in the profits as well as its fulfillment, due to the fact that such right is not only referred to the distributed profits, but it also encloses part of the profit that engender economic benefits to the shareholders, due to the increase of the equity value of their shares, even though such profit is held back in the company.The third chapter deeply analyses the right of the shareholder to participate in the profits already distributed, not only as a right to dividend to be discussed, but also as a right to the payment of dividends already declared. This last chapter analyzes the legal nature of the dividend to be discussed, the dividends already declared and the interest on net equity paid to the shareholders. The mandatory dividends (section 202 of Law 6.404/76) and the preferred dividends in all of their modalities (sections 17 and 203 of Law 6.404/76) are also studied in this chapter, as well as the rights entitled to them